МОТИВ ТУШУНЧАСИ ВА УНИНГ АДАБИЁТШУНОСЛИКДАГИ ТАЛҚИНЛАРИ - Кучкаров, О.А. (SCIENCE and SOCIETY, 2020)
In the article, the author discusses the concept of motive and its interpretation in the literature, genesis, functions, place in the poetic system. In the article the author analyzes the views of some Western scholars that have caused controversy about motives, and substantiated comments are given.
Keywords: motive; plot; schematic formula; dichotomous concept; invariant; fable